PWE-281 Are patients with cancers 'missed' on faecal occult blood (FOB) testing truly asymptomatic? – a multicentre analysis. (22nd June 2015) - George, AT; Aggarwal, S; Dube, M; Menon, A; Vogler, M; Logan, R; Field, A
Abstract : Introduction: We aimed to identify the symptomatology of patients who develop interval cancers (cancers diagnosed within 2 years of a negative FOBT screening) in the eligible population of the East Midlands region. Method: Data from the National Bowel Cancer Audit Programme from three tertiary colorectal centres (Queens Medical Centre, Nottingham; Royal Derby Hospital and Sherwood Forest Hospitals ll) in the FOB testing age group (60–74 years) over 2 years (August 2011 to August 2013) were analysed and linked to the regional FOB hub to identify patients who had developed colorectal cancer after a negative FOBT in the screening interval (2 years) status. Tumours from and distal to the splenic flexure were classed as left sided tumours. Dukes C/D tumours were classed as advanced tumours. All three centres were in incident rounds of screening. Results: The study covered a population of 2 million of which 200, 000 were eligible for screening. 521 colorectal cancers were diagnosed in the above population (0.11%). Of these, 231 cancers (44%) were in patients who had declined screening, 162 (31%) were picked up following on from a positive FOBT and 128 (25%) were picked up in patients who had a negative FOBT. Of these 128 patients (M: F; 84:44), median age 67 years (SD:3.8) the commonest presenting symptoms for these patients were change in bowel habits in 50(39%). Other presentations included bleeding per-rectum in 44 patients (34%), abdominal pain in 38 (30%) patients, anaemia in 36(28%) patients, loss of weight in14 (11%)patients, bowel obstruction in 13 (10%) patients, bowel perforation in 3(2%) patients. Only two patients were truly asymptomatic from the bowel cancer with this being identified in one patient during surgery for an ovarian cyst and during a trauma laparotomy in the other patient. In the 28% patients who had anaemia the blood picture included a Hb (mean)of 10.3gm;MCV of 82.4 and;MCH of 26.3. In 61% of anaemic patients, the cancer was located on the right side of the colon with an equal percentage being of advanced Duke's stage. The median interval between the negative FOB test and the diagnosis of cancer in these patients was 15 months (range 0.5–24 months). Conclusion: Our findings suggest that the majority of patients with 'missed' interval cancers were symptomatic with 'red flag symptoms' inspite of the negative FOB test. We also raise the possibility of a natural bias of subjects volunteering for the FOB test in that some who opt for the test may not be 'truly' asymptomatic but may have bowel symptoms not yet discussed with their general practitioner. We highlight the need for improved awareness to reduce delays in symptomatic patients seeking medical advice against a background of a negative FOBT. Disclosure of interest: None Declared.